2012
DOI: 10.1007/s00203-012-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength dependence of biological damage induced by UV radiation on bacteria

Abstract: The biological effects of UV radiation of different wavelengths (UVA, UVB and UVC) were assessed in nine bacterial isolates displaying different UV sensitivities. Biological effects (survival and activity) and molecular markers of oxidative stress [DNA strand breakage (DSB), generation of reactive oxygen species (ROS), oxidative damage to proteins and lipids, and the activity of antioxidant enzymes catalase and superoxide dismutase] were quantified and statistically analyzed in order to identify the major dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
149
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 65 publications
9
149
0
1
Order By: Relevance
“…These results suggest that UVC irradiation could induce ROS production in rats and lead to perturbation of prooxidant and antioxidant balance, in which the oxidant amount was outweighing the antioxidant defense. These findings are corroborated by the study of Santos et al in which UVC was able to induce the generation of ROS, lipid peroxidation (TBARS), DNA damage, and reduced SOD enzyme activity 28 . According to this finding and its regression analysis, the authors suggested that biological damage was induced by UV irradiation on bacteria is wavelength dependent and revealed that inactivation of cellular bacteria by UVC was caused by the increase in ROS level together with DNA damage.…”
Section: Discussionsupporting
confidence: 73%
“…These results suggest that UVC irradiation could induce ROS production in rats and lead to perturbation of prooxidant and antioxidant balance, in which the oxidant amount was outweighing the antioxidant defense. These findings are corroborated by the study of Santos et al in which UVC was able to induce the generation of ROS, lipid peroxidation (TBARS), DNA damage, and reduced SOD enzyme activity 28 . According to this finding and its regression analysis, the authors suggested that biological damage was induced by UV irradiation on bacteria is wavelength dependent and revealed that inactivation of cellular bacteria by UVC was caused by the increase in ROS level together with DNA damage.…”
Section: Discussionsupporting
confidence: 73%
“…, and H 2 O 2 were increased in dose dependent manner. It was supported by study reported by Santos AL in which irradiation with UVA, UVB, or UVC on bacteria increased in ROS production and DNA double strand breaks was occurred in dose dependent trend 32 .…”
Section: Discussionsupporting
confidence: 54%
“…Viability is lost rapidly due to damage to one or more critical cellular components, but other cellular components are left intact. Examples include shortwave UV damage to DNA (25), inactivation of the respiratory chain by solar disinfection (26,27), denaturation of critical catabolic or metabolic machinery by low-temperature pasteurization (28), and inhibition of DNA, RNA, or protein synthesis by antibiotics that bind tightly to specific enzymatic targets within one of these pathways. In these situations, bacterial cells can remain visibly intact and impermeable to PMA and PI for hours or days after viability is lost.…”
mentioning
confidence: 99%